(untitled) (Research, Society and Development, 2021)
This article aims to identify the importance of Home Care (HC), together with the challenges of this therapeutic modality in promoting the health of the elderly. The methodology consisted of a literature review in the narrative modality, which has a descriptive-discursive character. The BVS, SciELO and LILACS databases were used as a research source. The occurrence of home care is higher in women, elderly women, with chronic diseases (such as hypertension, diabetes) associated with comorbidities and a history of falls and hospitalization. The results point to a need to change the institutionalized health model, to reduce hospital costs and a need for patient-centered care and its relationship with the living space itself through HC. Concomitant to this, results consign the need to face the challenges that it brings such as the incessant weariness of the caregiver, who has little information and guidance on how to care, besides the own difficulties and barriers of the elderly’s territory, making care difficult and making more complex epidemiological picture. It concludes the need to deepen the discussion of several issues that cover HC, and the importance of restructuring access with an emphasis on the integrality of the elderly’s health and the important actors in this process: the caregiver, the family and the health team.